Unusual Presentation of a Small-Cell Variant of Anaplastic Large-Cell Lymphoma Case: When a Septic Picture Is Not Sepsis - Zhou Yu; Yifan Pang; Linda Wang; Daniel E. Ezekwudo; Foluso Ogunleye; Susanna S. Gaikazian; Mark Micale; James Huang; Ann Marie Blenc; Ishmael Jaiyesimi (Case Reports in Hematology)
We report a case of a small-cell variant of anaplastic large-cell lymphoma, with an unusual clinical presentation mimicking sepsis and a fulminant clinic course, in a 48-year-old Caucasian female. In this report, we discuss the diagnostic challenge, histopathologic features, and unique cytogenetic features of this case, in order to raise awareness of this rare presentation and emphasize the importance of meticulous peripheral smear examination and early bone marrow evaluation.